Status of Plankton in Impoundments in Major Reservoirs of Andhra Pradesh - P.K., Sukumaran; A.K., Das (Fishery Technology, 2025)
Seasonal variations in the composition and distribution of plankton of some selected reservoirs in Andhra Pradesh are reported. Zooplankton was dominant in all the nine reservoirs surveyed while phytoplankton was, in general, poor. Post-monsoon samples had maximum standing crop and it was minimum during monsoon. The reservoirs showed two pulses of plankton during post-monsoon and pre-monsoon periods.